PEMANFAATAN UDARA BUANG EXHAUST FAN SEBAGAI PEMBANGKIT LISTRIK TENAGA BAYU DENGAN PENAMBAHAN WIND TUNNEL BERBASIS ATMEGA 2560 - Satria Tresnajaya, Made; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p7, 2020)
Energy needs from year to year has increased along with the increase of population, economic growth, and high energy consumption. Until now, the world still depends on fossil fuels, this causes the depletion of oil availability and also causes air pollution. As a developing country, many industries are running around us and also many new industries are growing every day. Every industry generally has an exhaust fan to maintain the temperature of the work space. This exhaust fan works to remove air from the inside out. This research uses exhaust fan exhaust by using a 2-blade turbine and the addition of a wind tunnel, which will later compare the output between using a wind tunnel and without using a wind tunnel. In the research the use of exhaust fan exhaust air without using a wind tunnel to get an output of 0,30625W while with the addition of wind tunnel output increased by 8,25% to 0,76176W.